A prospective analysis of optimal total weight gain ranges and trimester-specific weight gain rates for Chinese pregnant women - Yunhui Gong; Yujie Xu; Ke Wan; Yidi Wang; Linan Zeng; Kun Zou; Yue Chen; Dagang Yang; Jingyuan Xiong; Li Zhao; Lingli Zhang; Toshio Shimokawa; et al. (BMC, 2023)
Abstract Background Gestational weight gain (GWG) criteria recommended by the Institute of Medicine may not be appropriate for Asians. Our aims are to investigate the association between GWG and adverse pregnancy outcomes, and to propose optimal total GWG and rates of GWG for Chinese women. Methods Prospective data of 51,125 mother-child pairs from 27 hospitals and community health care centers from Guizhou, Yunnan and Sichuan provinces in China between 2014 and 2018 were analyzed. Generalized Additive Models were performed to determine the associations of GWG with the risk of aggregated adverse outcomes (gestational diabetes mellitus, preeclampsia, cesarean delivery, stillbirth, preterm birth, macrosomia, large for gestational age, and small for gestational age). The range that did not exceed a 2.5% increase from the lowest risk of aggregated adverse outcomes was defined as the optimal GWG range. Results Among all participants, U-shaped prospective association was found between GWG and the risk of aggregated adverse pregnancy outcomes. The optimal GWG range of 8.2-13.0 kg was proposed for underweight, 7.3-12.5 kg for normal weight, and 2.0-9.4 kg for overweight/obese women. Meanwhile, a higher GWG rate in the first two trimesters than that in the last trimester was suggested, except for overweight/obese women. After stratified by maternal age, mothers ≥35 years were suggested to gain less weight compared to younger mothers. Conclusions To keep a balance between maternal health and neonatal growth, optimal GWG ranges based on Asia-specific BMI categories was suggested for Chinese women with different pre-gravid BMIs and maternal ages.